Environmental Performance Reviews: Belarus - Nations Unies (United Nations, 2016)
This series assists countries to improve their environmental policies by making concrete recommendations for better policy design and implementation. It helps integrate environmental policies into sector-specific policies such as those in agriculture, energy, transport and health. The present publication contains the third Environmental Performance Review of Belarus. It takes stock of progress made by Belarus in the management of its environment since the country was reviewed for the second time in 2005. It assesses the implementation of the recommendations made in the second review. It also covers issues of specific importance to the country related to legal and policy frameworks, the financing of environmental policies, greening the economy, and integrating environmental concerns into selected sectors, in particular air protection, water management, waste management, biodiversity, forests and protected areas, energy, agriculture, transport, forestry, tourism, environmental education and education for sustainable development, human settlements and health.